Missing : A play - Kani, John (Book collections on Project MUSE., 2015)
Missing is the story of Robert Khalipa, an ANC cadre living in exile, who is very senior in the organisation but is left out of the negotiations and almost forgotten in Sweden. Robert has a wealthy Swedish wife, Anna, and they have a daughter who is a practising doctor in a hospital in Stockholm. There is also Robertu2019s protege Peter Tshabalala, junior in the organisation, yet he gets the call to return to South African to join the democratic government. What follows is a story of conspiracies, lies, back stabbing and disappointments. Robert and his family are faced with the challenges of a South Africa that has changed radically from the one he remembers from more than thirty years ago. The government, in his opinion, does not seem to uphold the principles enshrined in the Freedom Charter. There is also conflict within his own family. Robert wants to stay in South Africa, while his wife and daughter want to go back to Sweden. Their love is tested to breaking point and difficult decisions have to be made by every individual. As with Kaniu2019s very successful and often-performed previous play, Nothing but the Truth, the ambiguities of freedom and of personal commitment are explored in this play.